Ultra-Endurance Associated With Moderate Exercise in Rats Induces Cerebellar Oxidative Stress and Impairs Reactive GFAP Isoform Profile - de Souza, Raphael Fabricio; Augusto, Ricielle Lopes; de Moraes, Silvia Regina Arruda; de Souza, Fabio Borges; Gonçalves, Lílian Vanessa da Penha; Pereira, Danielle Dutra; Moreno, Gisele Machado Magalhães; de Souza, Fernanda Maria Araujo; Andrade-da-Costa, Belmira Lara da Silveira (Frontiers in Molecular Neuroscience, 2020)
Ultra-endurance (UE) has been associated with brain metabolic changes, but it is still unknown which regions are vulnerable. This study investigated whether high race volumes in rodents, even under moderate intensity, can induce cerebellar oxidative and inflammatory status. Forty-five adult rats were divided into 6 groups according to training period, followed or not by an exhaustion test (ET) that simulates UE: control (C), control+ET (C-ET), moderate training volume (MV) and MV-ET, high training volume (HV) and HV-ET. A continuous running on a treadmill was performed 5 times/week. The training period was 30 (MV) and 90 (HV) min/day for 3 months. After 24h, the ET was performed and serum lactate levels were evaluated. Serum and cerebellar homogenates were obtained 24h after ET. Serum creatine kinase (CK), lactate dehydrogenase (LDH) and corticosterone levels were assessed. Lipoperoxidation (LP), nitric oxide (NO), Interleukin 1β (IL-1β) and GFAP proteins, reduced (GSH), oxidized (GSSG) glutathione levels, superoxide dismutase (SOD) and catalase (CAT) activities were quantified in the cerebellum. Serum lactate concentrations were lower in MV-ET (~20%) and HV-ET (~40%) compared to C-ET group. CK and corticosterone levels were increased more than ~2 fold by HV training compared to control. ET increased CK levels in MV-ET vs MV group (p=0.026). HV induced higher LP levels (~40%) but an additive effect of ET was only seen in the MV-ET group (p=0.02). SOD was higher in all trained groups vs C and C-ET (P <0.05). CAT, however, was intensified only in the MV group (P<0.02). The 50 kDa GFAP levels were enhanced in C-ET and MV-ET vs respective controls, while 42 kDa (~40%) and 39 kDa (~26%) isoform levels were reduced. In the HV-ET group, the 50 KDa isoform amount was reduced ~40-60% compared to the other groups and 39 KDa isoform increased ~7fold. LDH, IL-1β levels, GSH/GSSG and NO production were not modified. Cerebellar resilience to oxidative damage may be maintained under MV training, Data shows that but it is reduced by UE running. HV per se induced systemic metabolic changes and cerebellar oxidative status. UE after HV training was able to impair the cerebellum astrocyte reactive profile.